Ningmitai capsule in patients with chronic prostatitis/chronic pelvic pain syndrome: a multicenter, prospective, randomized, parallel, positive-controlled study - Gao, Jingjing; Zhang, Yao; Du, Junhua; Liu, Qiang; Cheng, Yi; Yang, Wentao; Wang, Daoyuan; Wang, Wei; Zheng, Liang; Wang, Dong; Wu, Lixin; Jiang, Xiaolei; et al. (Frontiers in Pharmacology, 2025)
BackgroundCP/CPPS is characterized by pain, the primary symptom, which significantly affects QoL and disrupts lower urinary tract function. Conventional monotherapies are often ineffective, necessitating multimodal treatments targeting key symptoms.MethodsThis multicenter, prospective, randomized, parallel, positive-controlled trial enrolled 323 men aged 18–60 years with CP/CPPS across 14 centers in China. Participants were randomly assigned to three groups: tamsulosin 0.2 mg daily, Ningmitai capsule (NMT) 1.52 g thrice daily, or a combination of both, for 8 weeks. The primary endpoint was the change in the total NIH-CPSI score from baseline to week 8. Secondary endpoints included changes in pain, urinary, QoL subdomains, the percentage of patients achieving a ≥25% reduction in NIH-CPSI total score, and pain scores. Safety was monitored through adverse events and liver function tests.ResultsOf the 323 patients, 108 received tamsulosin, 109 NMT, and 106 combination therapy. After 8 weeks, both NMT and combination therapy demonstrated significantly greater reductions in total NIH-CPSI scores compared to tamsulosin (−11.44 vs. −8.58, P < 0.001; −11.94 vs. −8.58, P < 0.001). Combination therapy also significantly reduced pain (P = 0.001) and improved QoL (P < 0.001) compared to tamsulosin. The NMT group showed greater improvements in pain scores at both 4 and 8 weeks compared to tamsulosin (P < 0.05). At week 8, the percentage of patients achieving a ≥25% reduction in NIH-CPSI total score was significantly higher in the NMT (78.64% vs. 55.91%, P < 0.001) and combination groups (82.83% vs. 55.91%, P < 0.001). Subgroup analyses indicated that NMT was most effective in patients with mild to moderate CP/CPPS, younger age (18–34 years), and disease duration of <12 months. No serious adverse events occurred, and NMT was well-tolerated across all groups.ConclusionNMT demonstrated superior efficacy over tamsulosin in reducing pain and improving QoL in CP/CPPS patients. Combination therapy provided enhanced symptom relief, particularly in micturition and QoL domains, supporting a multimodal approach for more effective CP/CPPS management. These findings validate NMT as a promising treatment, either alone or in combination, for CP/CPPS. Further long-term studies are needed to optimize its use.Clinical Trial RegistrationClinicalTrials.gov, identifier NCT05890235.